Recent mathematical methods in nonlinear wave propagation lectures given at the 1st session of the Centro internazionale matematico estivo (C.I.M.E.), held in Montecatini Terme, Italy, May 23-31, 1994 - Boillat, G. (Guy); Ruggeri, Tommaso (Lecture notes in mathematics (Springer-Verlag), 1996)
These lecture notes of the courses presented at the first CIME session of 1994 consider the state of the art in mathematical models in nonlinear wave propagation.